Pedestrian forward projection after vehicle collision - Piloto, P.A.G. (2020)
This paper is focused in the assessment of the relation between the vehicle collision velocity, the pedestrian throw distance and the pedestrian injury, after vehicle–pedestrian collision with forward projection. A few parameters were considered, in particular the collision velocity (8), the pedestrian mass and height (8), and the mass of the vehicle (3). The results of the throw distance projection were compared using two solution methods (simple and advanced), the results of other authors and with 15 real data accident with forward projections. A total of 192 different conditions were simulated, being the results in good agreement. The injury of the pedestrian was calculated, based on two injury criteria (GSI and FFC), aiming to define a simple relation between pedestrian injury and the vehicle collision velocity.